2010
DOI: 10.1111/j.1540-4560.2009.01636.x
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Roles of Self-Fulfilling Prophecies, Stigma Consciousness, and Stereotype Threat in Linking Latino/a Ethnicity and Educational Outcomes

Abstract: Acculturation and ethnic identity may be associated with Latino/as' educational outcomes and be relevant to their lower levels of academic achievement. This article explores how these relationships might be mediated by considering several empirically supported and theory-based social psychological processes-the selffulfilling prophecy, stigma consciousness, and stereotype threat. These processes suggest specific mediational mechanisms that remain largely unexamined, thereby offering novel directions for resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 65 publications
3
70
1
1
Order By: Relevance
“…Research on the self-fulfilling prophecy and stereotype threat (e.g. Guyll et al, 2010) shows that Hispanic children are susceptible to perceived bias. Care needs to be taken to promote adaptive educational strategies when teaching children who may be stigmatised within their own ethnic group and across other races.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the self-fulfilling prophecy and stereotype threat (e.g. Guyll et al, 2010) shows that Hispanic children are susceptible to perceived bias. Care needs to be taken to promote adaptive educational strategies when teaching children who may be stigmatised within their own ethnic group and across other races.…”
Section: Discussionmentioning
confidence: 99%
“…Many are from first-or second-generation immigrant families and face multiple challenges associated with acculturation and education, including English language proficiency in the classroom and bicultural ethic identity development (Guyll, Madon, Prieto, & Scherr, 2010). In addition to being behind their Caucasian peers in terms of academic achievement and having higher school dropout rates (Fry, 2003), there is research demonstrating that self-esteem in Hispanic individuals is lower in comparison to Caucasian and African-American individuals (Gray-Little & Hafdahl, 2000;Twenge & Crocker, 2002).…”
mentioning
confidence: 98%
“…Shelton, Richeson, and Vorauer (2006), argued that people from an ethnic group that is often stereotyped possibly will react to identity threat through behaviors that will help them avoid stressful situations. Also, increased in-group identification may provide a way to moderate stereotype threat effects (Guyll, Madon, Prieto, & Scherr, 2010), and this is the case amongst the Baka of Southeastern Cameroon, based on my experience in the field. These variables just mentioned can consequently build the capability for a group of people who believe there is an imminent threat to their social group to manage such threats in ways that do not translate to negative experiences with regards to satisfaction with life, as observed in the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Shelton, Richeson, and Vorauer (2006) speculated that interethnic interactions and the threat of being perceived as stereotypical of one's ethnic group indicated that the way members of a stereotyped ethnic group respond to matters of identity threat can be exposed through behaviors that include avoidance, outgroup devaluation/derogation, and behavior modulation/regulation. Ethnic identity is an element of one's self-concept and conveys one's attachment to his or her ethnic group (Guyll, Madon, Prieto, & Scherr, 2010). Guyll, Madon, Prieto, and Scherr, have argued that the social identity theory of Tajfel (1981) posited that self-esteem was partially derived from one's perception that one's group had value.…”
Section: International Journal Of Research Studies In Psychology 73mentioning
confidence: 99%
“…Although it is known that Spanish language is a critical component of many Latinos' ethnic and cultural identities (Guyll et al, 2010;Sox, 2009), 31 U.S. states have passed bills identifying English as the official language (U.S. English, 2016). From a social justice perspective, this may make it increasingly difficult for Spanish-speaking students to succeed in an English-speaking classroom (Ratts et al, 2010).…”
Section: Language Barriersmentioning
confidence: 99%